Eco-Digital Sovereignty: Transforming Government Communication and Legal Advocacy for Environmental Justice in the Algorithmic Era - Zulaikha Zulaikha; Sri Astutik; Nevrettia Christantyawati; Suyatno Ladiqi; Jessica Angelina Br Sitanggang (Jogjakarta Communication Conference (JCC), 2026)
This study explores the remaking of government communication in response to the climate crisis by transforming the problem posed by algorithmic hegemony (that public policy information fails to reach its audience because of the commercial biases of global platforms’ algorithms) into a case for “digital sovereignty” and the “radical retelling of who the state is in public communication about ecological questions.” Eco-digital sovereignty is a democratic imperative, not merely a technological transition. By providing agencies with the tools for clarity, governance recovers the digital commons for environmental justice. In what ways do they protect the ecologies of truth from the deluge of the alert economy? This study presents a framework for eco-digital sovereignty at the intersection of law and government communication. A qualitative juridical-communicative analysis illustrates the entanglement of state advocacy for the environment on the one hand and platform governance on the other. The analysis uncovers the necessity for government communication to shift from one-to-many broadcasting to an